Nationally Determined Contributions under the Paris Agreement and the costs of delayed action. (14th September 2019) - Winning, Matthew; Price, James; Ekins, Paul; Pye, Steve; Glynn, James; Watson, Jim; McGlade, Christophe
ABSTRACT: Current country-level commitments under the Paris Agreement fall short of putting the world on a required trajectory to stay below a 2°C temperature increase compared to pre-industrial levels by the end of the century. Therefore, the timing of increased ambition is hugely important and as such this paper analyses the impact of both the short and long-term goals of the Paris Agreement on global emissions and economic growth. Using the hybrid TIAM-UCL-MSA model we consider the achievement of a 2°C target against a baseline of the Nationally Determined Contributions (NDCs) while also considering the timing of increased ambition of the NDCs by 2030 and the impacts of cost reductions of key low-carbon technologies. We find that the rate of emissions reduction ambition required between 2030 and 2050 is almost double when the NDCs are achieved but not ratcheted up until 2030, and leads to lower levels of economic growth throughout the rest of the century. However, if action is taken immediately and is accompanied by increasingly rapid low-carbon technology cost reductions, then there is almost no difference in GDP compared to the path suggested by the current NDC commitments. Key policy insights Delaying the additional action needed to achieve the 2°C target until 2030 is shown to require twice the rate of emissions reductions between 2030 and 2050. Total cumulative GDP over the century is lower when additional action is delayed to 2030 and therefore has an overall negative impact on the economy, even without including climate change damages. Increased ratcheting of the NDC commitments should therefore be undertaken sooner rather than later, starting in conjunction with the 2023 Global Stocktake. Early action combined with cost reductions in key renewable energy technologies can reduce GDP losses to minimal levels (<1%). A 2°C future with technological advancements is clearly possible for a similar cost as a 3.3°C world without these advances, but with lower damages and losses from climate change.